Journal of international & global studies
Provides a multidisciplinary forum for the critical discussion and reflections on the consequences of globalization throughout the world. The editors welcome essays and book reviews that deal with globalization from economists, historians, political scientists, anthropologists, sociologists, geographers, linguists, religious, ethnic, or environmental studies specialists, cross-cultural education, media and communication researchers, or other humanities or social science scholars that have an international and global focus. One of our goals is to help undermine the fragmentation of specialization within the international academy by emphasizing broad interdisciplinary approaches to the comprehension of globalization in all of its many different forms and implications for different regions of the world.